SOSIALISASI BERSAMA KELOMPOK WANITA TANI KELURAHAN SRENGAT TENTANG PEMBUATAN PESTISIDA NABATI - Nurjanah Nurjanah; Siti Wahyuningsih Siti Wahyuningsih; Vivin Tri Nadya Vivin Tri Nadya; Elmina Praptika Melati Elmina Praptika Melati (JURNAL DAYA-MAS, 2022)
The Women Farmers Group (KWT) of Sekar Taji are mostly housewives or farmers in Srengat Village, Srengat District, Blitar Regency. Located on Jl. Mayang Rt 01 Rw 08 Krebet Village environment 4. Has good potential for horticultural cultivation and ornamental plants. The beginning of the establishment of this group was due to the effect of soaring chili prices in 2016 which affected local farmers greatly, then the village head Inggit Budi Santoso took the initiative so that every family or house has its own chili plant at least 5 trees. Over time, this group received Orchid Flower droppings from the Department of Agriculture with the aim of increasing the family’s income. One of the problems with the Sekar Taji farmer group is the problem of marketing orchids and the presence of pests and pathogens. Control is usually carried out by farmers by spraying synthetic pesticides. In this socialization process, we provide an alternative, namely using plant-based pesticides that are more environmentally friendly, through training on the manufacture of plant-based pesticides. The methods used are consultation, training and application. The result of this socialization is an increase in knowledge and skills about the benefits and ways of making vegetable pesticides from plants around the house. Vegetable pesticides can reduce production costs and have potential as a home industry.